Measuring xenon in human plasma and blood by gas chromatography/mass spectrometry. (22nd May 2014) - Thevis, Mario; Piper, Thomas; Geyer, Hans; Thomas, Andreas; Schaefer, Maximilian S.; Kienbaum, Peter; Schänzer, Wilhelm
<x xml:space="preserve">Abstract</x> RATIONALE Due to the favorable pharmacokinetic properties and minimal side effects of xenon, its use in modern anesthesia has been well accepted, and recent studies further demonstrated the intra‐ and postoperative neuro‐, cardio‐, and reno‐protective action of the noble gas. Since the production of the hypoxia‐inducible factor 1α (HIF‐1α) and its downstream effector erythropoietin as well as noradrenalin reuptake inhibition have been found to play key roles in this context, the question arose as to whether the use of xenon is a matter for doping controls and preventive doping research. The aim of the present study was hence to evaluate whether the (ab)use of xenon can be detected from doping control samples with the instrumentation commonly available in sports drug testing laboratories. METHODS Plasma was saturated with xenon according to reported protocols, and the target analyte was measured by means of gas chromatography/time‐of‐flight and triple quadrupole mass spectrometry with headspace injection. Recording the accurate mass of three major xenon isotopes at m/z 128.9048, 130.9045 and 131.9042 allowed for the unequivocal identification of the analyte and the detection assay was characterized concerning limit of detection (LOD), intraday precision, and specificity as well as analyte recovery under different storage conditions. RESULTS Xenon was detected in fortified plasma samples with detection limits of approximately 0.5 nmol/mL to 50 nmol/mL, depending on the type of mass spectrometer used. The method characteristics of intraday precision (coefficient of variation <20%) and specificity demonstrated the fitness‐for‐purpose of the analytical approach to unambiguously detect xenon at non‐physiological concentrations in human plasma and blood. Eventually, authentic plasma and blood samples collected pre‐, intra‐, and post‐operative (4, 8, and 24 h) were positively analyzed after storage for up to 30 h, and provided proof‐of‐concept for the developed assay. CONCLUSIONS If relevant to doping controls, xenon can be determined from plasma and blood samples, i.e. common specimens of routine sports drug testing in the context of Athlete Biological Passport (ABP) analyses. Optimization of sampling and analytical procedures will allow the detection limit to be further improved and potentially enable accurate quantification of the anesthetic agent. Copyright © 2014 John Wiley & Sons, Ltd.